Moskaus Spuren in Ostdeutschland 1945 bis 1949. Aktenerschließung und Forschungspläne - Scherstjanoi, Elke 1956- (Zeitgeschichte im Gespräch, 2015)
As research conditions in Russian archives began to improve in the mid-1990s, empirical studies were undertaken in Germany on Soviet occupation policy in Germany and on the Soviet military administration. This volume discusses important projects, cites deficiencies, and outlines future perspectives, thereby providing an initial assessment of the research